Política e PNUD: resiliência, desenvolvimento humano e vulnerabilidades - Wilke, Helena Cecília Barreto Bruno (2017)
This research surveys the development of the fundamental concepts and guidelines of the United Nations Development Program (UNDP). Its creation dates back to a period of liberalism and expanding of international organizations, seeking for democratic peace, still under the effects of World War II. Its purposes are correlated to designs created after the Cold War, when security and development, which were based on anthropological concepts, begin to respond to the restructuring of the planetary governmentality. The Human Development Index (HDI), adopted by the UNDP since the 1990s, is an important tool in identifying and constructing the so-called vulnerabilities as threats both for local and global governments. The survey of the Conjunct Program “Segurança com Cidadania”, coordinated by the UNDP in a neighborhood of Vitória, Espírito Santo, Brazil, disclosure the operational model of the HDI, together with the so-called “segurança cidadã” specifically designed for Latin America, which was recently incorporated to the Sustainable Development Objectives (SDO). The Restorative Justice is considered a complementary planetary connection aiming to broaden the formal penal system, flexibilizing sentences and implementing social policies in schools and communities. The present study verified the UNDP's effectiveness in enforcing penal practices operated in the name of the alleged neutrality of human development throughout the manufacture of responsible and resilient conducts that underpins the management of collective misery